Characterization of Nosocomial Infection in a Pediatric Intensive Care Unit. Cienfuegos 2005-2009 - Lourdes Elena Duany Badell; Dagmaris Losa Pérez; Mabel Ávila Ramírez; Jorge Emilio Barletta del Castillo; Sara Hernández Malpica; Aymahara Gómez Morejón (Medisur)
Background: children can frequently develop nosocomial infections in pediatric intensive care units. Objective: to characterize nosocomial infections in pediatric patients treated in intensive care units. Methods: a retrospective case series study was conducted in the Intensive Care Unit at Pediatric Hospital of Cienfuegos, between 2005 and 2009. The sample consisted of 70 patients who developed nosocomial sepsis and were admitted directly to the service. The variables studied were age, procedures performed during hospitalization, type of sepsis by site, isolated germs, microbiological support (microbiology tests) and condition at discharge (recovered or deceased). Results: nosocomial infections showed a rate of 3.2 per 100 patients discharged. Children under 1 year (41.4 %) were the most frequently affected. Pneumonia associated with mechanical ventilation was the most common infection (29.4%). Venous catheterization was used in all cases. Microbiology tests were performed in 84.2 % of cases, 85.3% of them had a positive result. Pseudomonas aeruginosa was the most frequently isolated bacteria and was also associated with highest mortality. Conclusion: nosocomial sepsis in this service was more frequent in children under one year, as a result of mechanical ventilation. Malnutrition and chronic illness were an important predisposing factor in these patients.